2011
DOI: 10.1673/031.011.12101
|View full text |Cite
|
Sign up to set email alerts
|

South American Spider Mites: New Hosts and Localities

Abstract: In order to contribute to taxonomic information on Tetranychid mites (Acari: Tetranychidae) in South America, surveys were conducted in Brazil (15 States and the Federal District) and Uruguay (one Department); 550 samples of 120 plant species were collected. Tetranychid mite infestations were confirmed in 204 samples, and 22 species belonging to seven genera of the Bryobiinae and Tetranychinae subfamilies were identified on 58 different host plants. Thirty-six new plant hosts were found in Brazil, South Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
(60 reference statements)
0
13
0
1
Order By: Relevance
“…Tetranychus urticae was associated with the species Ambrosia polystachya D.C. Asteracea (ragweed); Parthenium sp. Asteracea (parthenium); Pyrostegia venusta Miers Bignoniaceae (flame vine); Phaseolus lunatus L. Fabaceae (lima beans); Macroptilium atropurpureum (L.) Fabaceae (siratro); Passiflora edulis Sims Passifloraceae (yellow passion fruit); Triticum aestivum L. Poaceae (wheat); Alpinia purpurata K. Schum Zingiberaceae (alpinia) and Lantana camara L. Verbenaceae (wild sage) (Mendonça et al, 2011). The species T. ludeni and T. urticae occur together and have potential to cause severe damage and death to sweet potato plants cultivated in Brazil.…”
Section: Attack Of Two New Spider Mites On Sweet Potato (Ipomoea Batamentioning
confidence: 99%
“…Tetranychus urticae was associated with the species Ambrosia polystachya D.C. Asteracea (ragweed); Parthenium sp. Asteracea (parthenium); Pyrostegia venusta Miers Bignoniaceae (flame vine); Phaseolus lunatus L. Fabaceae (lima beans); Macroptilium atropurpureum (L.) Fabaceae (siratro); Passiflora edulis Sims Passifloraceae (yellow passion fruit); Triticum aestivum L. Poaceae (wheat); Alpinia purpurata K. Schum Zingiberaceae (alpinia) and Lantana camara L. Verbenaceae (wild sage) (Mendonça et al, 2011). The species T. ludeni and T. urticae occur together and have potential to cause severe damage and death to sweet potato plants cultivated in Brazil.…”
Section: Attack Of Two New Spider Mites On Sweet Potato (Ipomoea Batamentioning
confidence: 99%
“…Generally, in South America insect pests are a limiting factor adversely affecting the agricultural production of Fabaceae, especially in genus Phaseolus. For example, Aphis craccivora Koch (Hemiptera: Aphididae), as well as the phytophagous mites Eutetranychus banksi (McGregor) (Acari: Tetranychidae) and Tetranychus urticae Koch (Acari: Tetranychidae) (Coceano et al 1998;Mendonça et al 2011) have been reported to severely affect the production of several bean species.…”
Section: Natural Enemies Associated With Phaseolus Lunatus L (Fabacementioning
confidence: 99%
“…Mites herbivores are common pest in agriculture (Ghazy and Suzuki, 2014;Navia et al, 2009), ornamental plants (Silva et al, 2009) and forests (Pereira et al, 2012;Deus et al, 2012) infesting a wide range of plant hosts (Mendonça et al, 2011) and are among the most important pests across the world. Tetranychus ludeni Zacher (Acari: Tetranychidae) commonly found in the tropics (Zhang, 2002), occurs worldwide and infests more than 250 plant species (Gotoh et al, 2015), especially eggplant (Solanum melongena) and okra (Abelmoschus esculentus) (Reddy, 2001).…”
Section: Introductionmentioning
confidence: 99%